JURIDICAL ANALYSIS OF THE CRIMINAL OFFENSE OF HAZARDOUS AND TOXIC WASTE (B3) MANAGEMENT WITHOUT A PERMIT BY CV. JULIANA: A STUDY OF DECISION NUMBER 538/PID.SUS/2017/PN MDN - Amzat Erwinsyah; Syahrul Bakti Harahap (Jurnal Ilmu Hukum dan Keadilan, 2026)
This study aims to juridically analyze the elements of the criminal offense of unauthorized hazardous and toxic waste (B3 waste) management committed by CV. Juliana, to examine the judges’ legal considerations in imposing criminal sanctions, to assess the implementation of the principle of proportionality in sentencing, and to identify juridical obstacles in the application of environmental criminal law based on Decision Number 538/Pid.Sus/2017/PN.Mdn. The results of the study indicate that the elements of the criminal offense of unauthorized B3 waste management in the a quo case were lawfully and convincingly fulfilled, and that CV. Juliana, as a business entity, could be held criminally liable. The judges’ considerations in imposing criminal sanctions took into account aspects of evidentiary assessment, the principle of legality, the precautionary principle, and environmental protection as a public interest. The application of the principle of proportionality in sentencing is reflected in the imposition of sanctions commensurate with the degree of culpability and the potential environmental impact, in line with environmental sentencing theory. Nevertheless, juridical obstacles remain in the enforcement of environmental criminal law, particularly with regard to technical evidentiary issues, corporate criminal liability, and inter-agency coordination, which require strategic efforts to enhance the effectiveness of environmental law enforcement.